Sadharanikaran Model vs Mathematical Model: Analyzing their Relevance in Context of Social Media - Shaw, Priya (Bodhi: An Interdisciplinary Journal, 2019)
The communication process varies according to cultural, political, economic, social, psychological, socio-economic factors from one country to another. The term ‘communication’, however, has been accepted globally though the pattern of communication differs from one society to another. Communication scientists have tried to define communication in a particular context of a particular society. In this study, therefore, Sadharanikaran model from the Eastern perspective and Shannon and Weaver model from the Western perspective have been chosen to study the difference in the pattern of communication. The elements of the models have been studied along with the context of technological communication with particular reference to social media such as Facebook, WhatsApp and Skype.